Viral Marketing on Hanasui Purchase Decisions: The Mediating Role of Brand Awareness - Wawa Nazwa Saputri; Kokom Komariah; Sopyan Saori (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the influence of Viral Marketing on the purchase decision of Hanasui skincare products, with Brand Awareness as a mediating variable. The research focuses on students of Universitas Muhammadiyah Sukabumi (UMMI) who are users of Hanasui skincare products. A quantitative approach was employed using an associative descriptive method. Data were collected through questionnaires distributed to 200 respondents selected using probability sampling techniques. The data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, version 3. The results show that Viral Marketing has a significant influence on Brand Awareness, with a path coefficient value (O = 0.855), a t-statistic of 32.25 (>1.654), and a p-value of 0.000 (< 0.05). Furthermore, Brand Awareness was found to have a significant influence on purchase decisions, with a path coefficient (O = 0.574), a t-statistic of 5.894 (> 1.654), and a p-value of 0.000 (<0.05). Additionally, Brand Awareness significantly mediates the relationship between Viral Marketing and purchase decisions, with an indirect effect value (O = 0.491), a t-statistic of 5.908 (>1.654), and a p-value of 0.000 (<0.05). In conclusion, an effective Viral Marketing strategy can enhance Brand Awareness, which in turn contributes to increased purchase decisions of Hanasui skincare products among UMMI students.